Dietary practices, attitudes, and physiological status of collegiate freshman football players - Jonnalagadda, S. S.; Rosenbloom, C. A.; Skinner, R. (The Journal of Strength and Conditioning Research, 2001)
The purpose of this study was to determine the dietary practices, attitudes, and physiological status of freshman collegiate football players. Thirty-one freshman football players at a National Collegiate Athletic Association division I school completed a self-administered nutrition screening questionnaire designed to determine their dietary practices and attitudes. Fasting blood samples were collected and height and weight were measured. The mean age of these athletes was 18 years. These players reported eating 3.6 times per day and on the average eating out 4.8 times per week. Fast food was the most common choice when eating out (55%). Of these athletes, 42% reported the use of dietary supplements, the most popular one being creatine (36%). Although more than 90% of the athletes recognized the importance of maintaining proper hydration status, greater than 50% believed that protein supplements were necessary for muscle growth and development, protein was the primary source of energy for muscle, and vitamin and mineral supplements increased energy levels. The plasma lipid profiles of the majority (76%) of the athletes were within normal ranges. The data suggest that these athletes may require education about healthy dietary practices and on the proper use of dietary supplements. This is not only important to help improve performance but to also promote healthy dietary practices in the long term.